Investigation of temporal variations in particle number concentrations of ambient air in Ankara and the relationship between particle number and mass concentrations - Yosuncığır, Caner. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2020., 2020)
In this study, temporal variations in the number and mass distribution of atmospheric particles are investigated. Particle number distribution of particles was measured using a laser spectrometer at every minute for 12 months. In addition to particle number measurements, PM2.5 and PM10 samples were collected at the same time and at the same location. Particle mass concentrations were measured in the collected samples. Statistical tests are used to determine factors affecting variations in particle number concentrations. The effect of meteorological variations and the effect of anthropogenic and natural events on particle count and mass concentration data are analyzed. In the study, a mathematical model is developed, based on the collected data, to convert the particle number concentration data to particle mass concentration data and evaluate the direct effect of meteorological data on the particle count concentration data. The model is verified by a detailed comparison of the results obtained from the model with the GRIMM mass concentration results.
Keywords: Air -- Pollution -- Turkey -- Ankara.; Atmospheric chemistry -- Turkey -- Ankara -- Measurement.; Environmental chemistry -- Turkey -- Ankara -- Mathematical models.; Particles -- Health aspects.